Filmmaking - Stoller, Bryan Michael (For dummies., 2020)
Everything you ever wanted to know about making a movie but were afraid to ask ... Lights, camera, action! We all have at least one movie in us, and the amazing and affordable advances in digital technology makes it increasingly easy to make your dream a reality and share it with the world. Filmmaking for Dummies is your definitive guide to bringing a project to life, from the comedy antics of loveable pets to the deepest, most meaningful independent film. Bryan Michael Stoller is your friend and guide, sharing his knowledge gained over 100 productions (directing and working with Dan Aykroyd, James Earl-Jones, Barbra Streisand and Drew Barrymore, among others) to show you how to take your movie from the planning and storyboarding stage, through shooting and editing, to making it available to your adoring audiences through television broadcast, streaming online or in movie theaters. For the do-it-your-selfer, the book includes tips on how to finance your project, a look at the latest software and apps, including advancements in digital technology, and for the passionate director, advice on how to hire and work with your cast and crew and find great scenic locations. Whether you want to become a professional filmmaker or just create great YouTube videos or nostalgic home movies, shooting with your smartphone or with consumer or pro-gear, this practical guide has it all. Learn how to compose your shots and when to move the camera. Make the perfect pitch to sell your story. Take advantage of helpful contacts and tons of new resources. Get up-to-date on the latest and greatest digital technology. Find the right distributor, or learn how you can be your own distributor! So, you really have no excuses to make your masterpiece. Get rolling with a copy of Filmmaking for Dummies today and start shooting for the stars!